BANK RESILIENCE AND POLITICAL INSTITUTIONS: DO BANKING BUSINESS MODELS MATTER? - Azmi, Wajahat; Ali, Mohsin; Islam, ‪Muhammad Umar (Journal of Islamic Monetary Economics and Finance, 2023)
This paper investigates the effect of political institutions on bank stability of dual banking countries.   Applying the two-step GMM approach to a panel sample of Islamic and conventional banks from 2005 to 2020, we arrive at the following results. First, we observe that the quality of political institutions leads to more stable banking system, which is in line with the view that quality political institutions improve the transparency, thereby reducing adverse selection and leading to overall improvement in the banking stability. Second, when we look at components of political institutions, we document the significance of the voice and accountability dimension in enhancing bank stability. Finally, as a side result, we find evidence that competition leads to stability for Islamic banks.  These findings are robust to several robustness tests. The implications of our findings are provided in the paper.